New Strategic Questions in European Security and the Aegean Neighbours - Bellou, Fotini (Études helléniques / Hellenic Studies, 2001)
Improvement in the relations of the two Aegean neighbors has been widely appreciated and has strengthened the strategic positions of both Greece and Turkey. In addition, Greece’s stance in the Helsinki European Council (December 10-11, 1999), not to veto Turkey’s inclusion in the group of candidate member-states to the European Union (EU) has served not only Greek and Turkish interests, but also has advanced the evolving security objectives of the EU. For this reason, as will be argued in this paper, Greek-Turkish relations and the degree of further rapprochement are becoming gradually intertwined with the new European security architecture. However, different priorities in the rationale of the two Aegean neighbors regarding the salience of Turkey’s inclusion in the group of EU candidate members, may affect the eventual outcome of the currently unfolding step-by-step peace process.